Peran Digital Literacy dalam Memediasi Pengaruh Technology Integration dan Collaborative Learning terhadap Hasil Belajar Akuntansi - Nadia Maulida; Pasca Dwi Putra; Sondang Aida Silalahi; Tuti Sriwedari; Haryani Pratiwi Sitompul (FKIP, Universitas Banten Jaya, 2026)
This study examines the influence of technology integration and collaborative learning on accounting students' learning outcomes at SMK Negeri 1 Patumbak, with digital literacy as a mediating variable. The urgency of this research stems from the fact that 54.4% of Grade X Accounting students failed to meet the Minimum Completeness Criteria (KKM) of 75, despite the application of digital-based learning and collaborative activities in the classroom. This study employed a quantitative ex post facto design involving all 68 Grade X Accounting and Financial Institution students through total sampling. Data were collected via a four-point Likert scale questionnaire and documentation of mid-semester exam scores, then analyzed using path analysis and Sobel test with SPSS version 31.0.2.0. Results showed that technology integration and collaborative learning each had a significant positive direct effect on both learning outcomes and digital literacy. Digital literacy itself proved to be the most dominant predictor of learning outcomes (β = 0.544). Furthermore, digital literacy significantly mediated the influence of technology integration (Z = 2.750, p = 0.006) and collaborative learning (Z = 4.460, p < 0.001) on learning outcomes, with partial mediation occurring in both pathways. These findings confirm that technology integration and collaborative learning enhance learning outcomes not only directly, but also indirectly by strengthening students' digital literacy as a cognitive bridge toward deeper conceptual understanding. These findings suggest that teachers should design technology use and collaborative activities not merely as instructional tools, but as deliberate pathways for building students' digital literacy, which in turn serves as a cognitive bridge toward deeper conceptual understanding and improved learning outcomes.